The Influence of Problem Based Learning Model on the Critical Thinking Elementary School - Ellen Widy Yuliasandra; Fitria Wulandari (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the influence and effect’s magnitude of Problem Based Learning on the critical thinking skills of fifth grade students at Jeruk Purut II Elementary School. The research method used is quantitative research with the type of Pre-Experimental Design and One Group Pretest-Posttest Design. The data collection technique uses a critical thinking ability test sheet consisting of 12 questions. Data analysis technique using paired sample t-test and ETA squared t test. The results of the pretest and posttest hypothesis testing showed a sig. (2-tailed) 0.00 which is less than 0.05 so that there is a significant effect of the Problem Based Learning model on critical thinking skills. Then, the eta squared calculation shows a value of 0.88 which is belong to very large category. The conclusion from the research results is that the Problem Based Learning model influences the critical thinking skills of fifth grade elementary school students and with effect’s magnitude belong to very large category.